EVALUASI PELAKSANAAN PENILAIAN AUTENTIK KURIKULUM 2013 MATA PELAJARAN KIMIA DI SMA NEGERI 1 BENAI: (Evalution of The Implementation of Authentic Curriculum 2013 Chemistry Subjects at SMAN 1 Benai) - Julia Rozanah. MY; Rosa Murwindra,; Asregi Asril (Perspektif Pendidikan dan Keguruan, 2019)
This research is an evaluation study with a quantitative descriptive approach that uses the Stake evaluation model. The purpose of this study was to determine the implementation of the 2013 authentic curriculum assessment and to find out the obstacles experienced by the teacher in carrying out the assessment in the learning process taking place on chemistry subjects in SMAN 1 Benai 1. The subjects of this study were 3 chemistry teachers at SMAN 1 Benai 1. Data collection techniques are documentation, observation and interviews. The data analysis technique in this study uses descriptions and uses the percentage formula to determine the assessment criteria. Based on the results of the study it can be concluded that the implementation of the 2013 curriculum authentic assessment on chemistry subjects in SMAN 1 Benai 1 obtained the percentage of implementation evaluation of 79.8% which was categorized as well implemented. The constraints experienced by chemistry teachers in carrying out authentic assessments are in the implementation of attitude assessments, the teacher feels difficulty in carrying out the assessment at the beginning of the semester precisely at the first 2 months to 3 months because it is not memorized by the names of students.